Design suggestions for a persuasive e-coaching application: A study on informal caregivers’ needs - Shweta Premanandan; Awais Ahmad; Åsa Cajander; Pär Ågerfalk; Lisette van Gemert-Pijnen (Digital Health, 2023)
Objective Informal caregivers such as relatives or close friends of patients are essential for caregiving at home. However, caregiving is a complex experience that may affect the caregivers’ well-being. Therefore, there is a need to provide support for caregivers, which we address in this article by proposing design suggestions for an e-coaching application. This study identifies the unmet needs of caregivers in Sweden and provides design suggestions for an e-coaching application using the persuasive system design (PSD) model. The PSD model offers a systematic approach to designing IT interventions. Methods A qualitative research design was used, and semi-structured interviews were conducted with 13 informal caregivers from different municipalities in Sweden. A thematic analysis was performed to analyze the data. The PSD model was used to map the needs emerging from this analysis to propose design suggestions for an e-coaching application for caregivers. Results Six needs were identified, and based on them, we proposed design suggestions for an e-coaching application using the PSD model. These unmet needs are monitoring and guidance, assistance to avail formal care services, access to practical information without being overwhelmed, feeling of community, access to informal support, and grief acceptance. The last two needs could not be mapped using the existing PSD model, resulting in an extended PSD model. Conclusion This study revealed the important needs of informal caregivers based on which design suggestions for an e-coaching application were presented. We also proposed an adapted PSD model. This adapted PSD model can be further used for designing digital interventions in caregiving.